Influence ofHelicobacter pyloriInfection on Gastrointestinal Hormone and Colon Motility of Rats. (May 2016) - Cui, Ning; Luo, Hesheng; Xia, Hong; Chen, Wei; Yu, Guang
ABSTRACT : Background: : The purpose of this study was to study the relationships among Hp infection, secretion of gastrointestinal hormones and contraction of colon muscles of Sprague Dawley rats. Helicobacter pylori (Hp) is proved to be a chief criminal of gastric diseases. It can even be detected outside upper digestive tract like lung and kidney. Scientists found that Hp might modulate hormone secretion by influencing brain‐gut axis. However, the specific relationships among Hp infection, hormone secretion and colonic motility are still undefined. Materials and Methods: : Hp infection procedures were completed by intragastric administration to male Sprague Dawley rats. All model groups' rats were confirmed of Hp infection by rapid urease test and gastric mucosa biopsy. Plasma hormones were determined using Enzyme Immunoassay Kits after Hp infection. Colonic motility was assessed by counting numbers of fecal pellet output and recording contractions of isolated colonic strips through isometric force transducer. Results: : Hp infection groups significantly increased fecal pellet output compared with negative Hp infection groups ( P < 0.05). The Hp infection groups' mean tension of spontaneous contraction of colon smooth muscle was significantly greater than the negative Hp infection groups' ( P < 0.05). Significant differences can be found between Hp infection groups and negative Hp infection groups, concerning the concentration of gastrin, cholecystokinin and substance P ( P < 0.05). Conclusions: : Hp infection probably activate the regulation of brain‐gut peptides and gastrointestinal hormones, which could interact with associated receptors in smooth muscle cells, leading to increased count of fecal pellet output and increased colon motility of smooth muscles.